PENGARUH LATIHAN INTERVAL DAN FARTLEK TERHADAP PENINGKATAN KAPASITAS VO2 MAKS PADA PEMAIN FUTSAL SMA WIDYAGAMA KOTA MALANG - Fahmi Andi Wiranata; Slamet Raharjo; Heri Purnama Pribadi (Program Studi Ilmu Keolahragaan, 2023)
When observing and interviewing coaches a problem was found in the futsal players at Widyagama High School Malang city, requires training that increases VO2 max or endurance to support performance when competing. The purpose of this study is to prove interval and fartlek training on increasing VO2 max. In this study using a one group pre test - post test design. The data instrument uses the Bleep Test. Determination of a sample of 15 subjects using total sampling. The exercises given within 6 weeks were 18 meetings. The pre-test data results obtained a mean of 43.360 and post-test data with a mean of 45.873 experienced an increase difference of 2.51. The hypothesis test used to determine the difference between pre-test and post-test is the Shapiro-Wilk test. The results of the significance test of 0.000 indicate that there is a significant difference, so it can be concluded from the results of the study that there is an effect of giving interval and fartlek training to increasing VO2 max futsal players at SMA Widyagama Malang City.